Anthelmintic activity of Moringa oleifera and Azadirachta indica against gastrointestinal nematodes of wild sheep - Rafique, Azhar; Mahmood, M. Shahid; Abbas, Rao Zahid; Ali, Sultan; Mian, AH; Rizwan, A (Journal of the Hellenic Veterinary Medical Society, 2022)
Gastrointestinal nematodes (GINs) are serious issue for health of wild sheep kept in captivity. Chemically synthesized anthelmintics are regularly used to control these parasites. In recent years anthelmintic resistance and remnant of drugs in animal products leads to use of medicinal plants as alternative to anthelmintics. In current study, the efficacy of aqueous, methanolic and ethanolic dried leaf extracts of medicinal plants Moringa oleifera and Azadirachta indica were tested for in vitro ovicidal and larvicidal activities against Haemonchus, Trichuris, Coccidia and Trichostrongylus; naturally acquired nematodes isolated from wild sheep (Ovis orientalis orientalis). Six concentrations of these plants extract (1.56, 3.13, 6.25, 12.5, 25 and 50 mg/ml) were evaluated using egg hatching assay (EHA) and larval development assay (LDA) in three replicates. To compare treatment effects, untreated and treated (0.1% ivermectin) controls were used. The aqueous, methanolic and ethanolic leaf extracts showed anthelmintic activities against isolated genera of nematodes but the inhibition was maximum (99%) in ethanol extract of M. oleifera followed by methanol extract (97%) at maximum concentration tested at (50mg/ml). The overall findings of this study shows that Moringa oleifera and Azadirachta indica leaf extracts possess significant anthelmintic efficacy against GINs of sheep and these could be a natural alternative to synthetic anthelmintics to treat the worm infections in animals.